Fire and fortitude the US Army in the Pacific War, 1941-1943 - McManus, John C. 1965- (Dutton Caliber, an imprint of Penguin Random House LLC, 2019)
"John C. McManus, one of our most highly-acclaimed historians of World War II, takes readers from Pearl Harbor...a rude awakening for a ragtag militia woefully unprepared for war...to Makin, a sliver of coral reef where the Army was tested against the increasingly-desperate Japanese. In between were nearly two years of punishing combat as the Army transformed, at times unsteadily, from an undertrained garrison force into an unstoppable juggernaut, and America evolved from an inward-looking nation into a global superpower."...Provided by publisher